Integrating New Technical Staff: Implications for Acquiring New Technology - Lee, Denis M. S.; Allen, Thomas J. (Management Science, 1982)
Hiring new staff in R&D provides an important opportunity for a firm to acquire new technological knowledge. It also takes a considerable length of time before new R&D staff become fully integrated into the organization. This study compares the communication patterns of new and veteran R&D staff as a function of their work activities. The results suggest that both the benefits and problems in the hiring and integration of new R&D staff is moderated by the type of research, development or technical service work involved. Particular attention should be paid to the integration of new staff involved in new product or process development, where the benefits of bringing in new people are great, but the communication barriers to overcome are also found to be the most serious.